Does concentration drive the scatter in the stellar-to-halo mass relation of galaxy clusters?. Issue 4 (17th June 2021) - Zu, Ying; Shan, Huanyuan; Zhang, Jun; Singh, Sukhdeep; Shao, Zhiwei; Chen, Xiaokai; Yao, Ji; Golden-Marx, Jesse B; Cui, Weiguang; Jullo, Eric; Kneib, Jean-Paul; Zhang, Pengjie; et al.
ABSTRACT: Concentration is one of the key dark matter halo properties that could drive the scatter in the stellar-to-halo mass relation of massive clusters. We derive robust photometric stellar masses for a sample of brightest central galaxies (BCGs) in SDSS redmapper clusters at 0.17 < z < 0.3, and split the clusters into two equal-halo mass subsamples by their BCG stellar mass M_*^BCG . The weak lensing profiles ΔΣ of the two cluster subsamples exhibit different slopes on scales below 1 h^-1 Mpc . To interpret such discrepancy, we perform a comprehensive Bayesian modelling of the two ΔΣ profiles by including different levels of miscentring effects between the two subsamples as informed by X-ray observations. We find that the two subsamples have the same average halo mass of 1.74× 10^14 h^-1 M_, but the concentration of the low-M_*^BCG clusters is 5.87_-0.60^+0.77, ∼1.5σ smaller than that of their high-M_*^BCG counterparts (6.95_-0.66^+0.78 ). Furthermore, both cluster weak lensing and cluster-galaxy cross-correlations indicate that the large-scale bias of the low-M_*^BCG, low-concentration clusters are 10 per cent higher than that of the high-M_*^BCG, high-concentration systems, hence possible evidence of the cluster assembly bias effect. Our results reveal a remarkable physical connection between the stellar mass within 20-30 h^-1 kpc, the dark matter mass within 200 h^-1 kpc, and the cosmic overdensity on scales above 10 h^-1 Mpc, enabling a key observational test of theories of co-evolution between massive clusters and their central galaxies.